Motivational Strategies Employed by Pre-Primary School English Teachers in Nepal - Rai, Koshi Raj; Karki, Tek Mani; Karki, Bishal (KMC Journal, 2022)
Motivation plays an important role in teaching learning activities. The motivational techniques make the classroom more interesting, effective, and successful as they help teachers teach the students effectively and students learn enthusiastically and interestingly. Considering the teaching learning activities using motivational techniques in the classroom, this paper explores the current practices of motivational strategies implemented by English teachers at the pre-primary level. A series of interviews with purposively selected pre-primary level English teachers and their class observations reveal various motivational strategies used in the teaching learning activities in the classrooms. The strategies the teachers used in their daily practices include greetings the students, playing with goods, using rhymes in the class, offering rewards, and calling lovely names to the students. The implication of the study is that the motivational strategies employed in the classroom activities are more effective, fruitful, and the students learn the teaching stuff in a joyful environment.